Prefrontal cortex neural activity predicts reduction of non-suicidal self-injury in adolescents with major depressive disorder: An event related potential study - Liu, Huishan; Wen, Yujiao; Liang, Xiumei; Xu, Yifan; Qiao, Dan; Yang, Chunxia; Han, Min; Li, Hong; Ren, Tian; Zhang, Xuemin; Li, Gaizhi; Liu, Zhifen (Frontiers in Neuroscience, 2022)
Background: Non-suicidal self-injury (NSSI) is common in adolescent MDD, which is also a risk factor for suicide. However, there is few research on biomarkers and predictors about treatment response of NSSI. The purpose of this study was to find the difference of P300 between adolescent MDD group with NSSI and healthy control group, and to explore whether the baseline electrophysiological level can predict the change of NSSI after treatment. Methods: We collected 75 first-episode drug-naïve MDD patients with NSSI (NSSI group) and 57 healthy controls (HC group). The general demographic data, self-injury frequency, HAMD score and electrophysiological level of NSSI group and HC group were collected. The frequency of NSSI in was also collected after 8 weeks of antidepressant treatment. Results: Compared to HC, the latency of the N1components was significantly prolonged, whereas the amplitude of P3b was decreased in the NSSI group (P<0.05). The frequency of self- injury decreased significantly after intervention (P<0.01). Regression analysis showed that the amplitudes of P3b had a significant positive predictive effect on the reduction of NSSI frequency after eight weeks, and P2 had a significant negative predictive effect on it. Conclusion: P2 and P3b markers at baseline can be used as potential predictors of the reduction of NSSI in adolescent with MDD.